Numerical Analysis of Resistance Acting on Sea-Going Pusher and Barge System - Sano, Masaaki; Kawano, Yusuke; Yamamoto, Takuto; Yasukawa, Hironori (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Because a pusher and barge system (P/B) can be divided into a pusher and a barge(s), the pusher does not need to wait for the completion of loading/unloading, and it can start the next voyage soon after arriving. Therefore, a good transportation efficiency can be expected. In these days, a P/B is also available to a sea-going service by developing a mechanical connection which enabled a P/B to achieve the seaworthy performance in waves. However, there is a concern that the navigation speed is usually less than same-size cargo ships. It may be due to significant vortices generated in the gap at the connection, but the mechanism is still unclear. From this viewpoint, in this study, CFD analysis was carried out to investigate the resistance performance associating with the flow and pressure fields around the pusher and barge, especially with focus on the gap between them. We discussed the unique change of the resistance characteristic depending on the barge load conditions.